Latin America Climate- Smart Villages AR4D sites: 2017 Inventory - Bonilla Findji, Osana; Martínez Barón, Deissy; Martínez, Jesús David; Castellanos, Andrea; Ortega, Luis A.; Suchini, J G; Paz, Liliana Patricia; Aguilar, Amílcar; Álvarez Toro, Patricia (2018)
Inventory of CSA practices in Latin America's Climate-Smart Villages.